How Race Is Made in America: Immigration, Citizenship, and the Historical Power of Racial Scripts - Natalia Molina (University of California Press, 2013)
How Race Is Made in America examines Mexican immigration from 1924 to 1965 in order to understand how race and citizenship were constructed during this crucial period. I demonstrate that what was unique about these years was the emergence of what I call an immigration regime that remade racial categories that still shape the way we think about race, and specifi cally Mexicans. Th rough an examination of a diverse array of legal, po liti cal, social, and cultural sources related to the immigration regime, I off er historical answers as to why Mexican Americans are still not deemed fully American and are largely equated with illegality. Th e period between 1924 and 1965 is fascinating for anyone interested in the evolution of racial identities in the United States. From 1917 to 1924 a series of legislative acts reduced immigration to the United States by 85 percent. ï›œ Th e year 1924 marks the passage of the capstone immigration act, the Johnson- Reed Immigration Act, which limited the number of immigrants permitted entry from specifi c countries, thereby drastically reducing the entry of southern and eastern Eu ro pe ans (mostly Jews), who were deemed inferior â€œbreeds.â€ Th e Act also prohibited groups deemed ineligible for naturalization, specifi cally Chinese, Japa nese, and other Asians, who were already facing severe immigration restrictions. Th e 1924 Immigration Act was the nationâ€™s fi rst comprehensive restriction law. It remapped the nation in terms of new ethnic and racial identities, specifi cally transforming denigrated Eu ro pe an ethnics into â€œwhitesâ€ while simultaneously criminalizing Mexicans as illegal workers who crossed into the United States without authorization.ï˜º In the four de cades that followed, immigration laws fundamentally shaped the pa ram e ters of race in America. I end my study in 1965, which ushered in a new immigration regime with the passage of the 1965 Immigration and Nationality Act, abolishing the quotas established by the 1924 Act.